MEMBANGUN KREATIFITAS ANAK DENGAN MEMBUAT MOZAIK DI DESA KARANG SATRIA - Fathia Rifdah; Jaka Waluya; Adrian Adrian; Rasminto Rasminto (Universitas Islam 45 Bekasi, 2022)
This paper contains a portrait of the creative education of today's children, given the increasingly sophisticated and development of existing technology. Today's children can also be called millennials. Millennials are children born between the 1980s and 2000s. Millennials are children who have many diverse abilities and creativity which of course can be developed in a positive way to hone their own abilities. Creativity is a child's experience in expressing themselves and actualizing individual identity in an integrated form, both relationships with themselves, with nature and with other people. Children's creativity needs to be built from an early age, so that children can get used to it and can improve children's mindsets to be creative. Therefore, the author raised a program to increase children's creativity by making mosaics through seeds and rice whose purpose is expected to make children express themselves through creative thinking through activities that can build creativity and of course very fun and can fill time with useful things besides that. can also increase self-ability for the future so that they can think creatively in solving a problem or making a project that will be useful later. This activity program was carried out in RW 10 Karang Satria Village with a period of 1 month which was divided into 3 meetings. The methods applied during this activity program are consultation and training. The results that can be seen from the implementation of this program are that it can make children express themselves and increase children's creativity through the pictures they make and decorate using grains and rice.